Understanding the release efficiency of Atlantic cod (Gadus morhua) from trawls with a square mesh panel: effects of panel area, panel position, and stimulation of escape response - Herrmann, Bent; Wienbeck, Harald; Karlsen, Junita; Stepputtis, Daniel; Dahm, Erdmann; Moderhak, Waldemar (ICES Journal of Marine Science, 2015)
Based on size selectivity data for more than 25 000 cod (Gadus morhua) collected during experimental trawl fishing with six different codends, all of which included a square mesh panel, we investigated the effect on cod-release efficiency based on the size of the square mesh panel area, position of the square mesh panel, and stimulation of the escape response. Based on the results, we were able to explain why the BACOMA codend, applied in the Baltic Sea cod directed trawl fishery, releases juvenile cod efficiently, whereas other designs, including a square mesh panel with similar mesh size, are less efficient. Our main findings reveal that the release efficiency of the square mesh panel in the BACOMA codend depends largely on the overlap of the square mesh panel and the catch-accumulation zone in the codend, where cod do not have the option of just drifting further back in the trawl when proximate to the panel. On the contrary, the reduction in panel size by 50% did not significantly affect the release efficiency when the panel overlapped with the catch-accumulation zone. It was possible to stimulate an escape response for cod to achieve a release through a square mesh panel positioned away from the catch-accumulation zone. Our findings demonstrated that this release was as efficient as for a panel mounted in the catch-accumulation zone of the codend. Devices that stimulate behaviour may improve the release efficiency of cod through square mesh panels in other fisheries where this is a problem.